The Last Enemy 1 Corinthians 15:19-26, John 20:1-18 - Marcus, Joel (The expository times, 2007)
The article presents Biblical reflections on Jesus Christ's death and resurrection in I Corinthians 15:19 and John 20:1-18. It questions Apostle Paul's claim that death has been destroyed through Jesus Christ's resurrection. It cites an article by sociologist Amitai Etzioni about the death of his wife and his son which was published in the October 7, 2006 issue of the "New York Times." It centered on the Easter story wherein Mary Magdalene goes to the tomb early on the first day of the week only to find out that Jesus Christ's body was not there.